Temperature Oscillation Modulated Self-Assembly of Periodic Concentric Layered Magnesium Carbonate Microparticles - Li, Shihong; Wang, Zheng Jim; Chang, Ting-Tung (PLOS ONE, 2014)
Intriguing patterns of periodic, concentric, layered, mineral microstructure are present in nature and organisms, yet they have elusive geneses. We hypothesize temperature oscillation can be an independent factor that causes the self-assembly of such patterns in mineral phases synthesized in solution. Static experiments verify that rhythmic concentric multi-layered magnesium carbonate microhemispheres can be synthesized from bicarbonate solution by temperature oscillation, without use of a chemical template, additive or gel-diffusion system. Appropriate reactant concentration and initial pH value can restrain the competitive growth of other mineral generations. Polarized light microscopy images indicate the microhemispheres are crystalline and the crystallinity increases with incubation time. The thickness of a single mineral layer of microhemisphere in microscale is precisely controlled by the waveform parameters of the temperature oscillation, while the layer number, which can reach tens to about one hundred, is constrained by the temperature oscillation period number. FT-IR spectra show that these microhemispheres synthesized under different conditions can be identified as the basic form of magnesium carbonate, hydromagnesite (Mg5(CO3)4(OH)2⋅4H2O). SEM images exhibit the characteristic microscopic texture of the alternating dark and light rings of these microhemispheres. TEM images and ED patterns suggest the nanoflakes of microhemispheres are present in polycrystalline form with some degree of oriented assembly. The temperature oscillation modulated self-assembly may offer a new mechanism to understand the formation of layered microstructure of minerals in solution, and provide a non-invasive and programmable means to synthesize hierarchically ordered materials.